2022
DOI: 10.1152/japplphysiol.00416.2021
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula compared with continuous positive airway pressure: a bench and physiological study

Abstract: High-flow nasal cannula (HFNC) is extensively used for acute respiratory failure. However, questions remain regarding its physiological effects. We explored 1) whether HFNC produced similar effects to continuous positive airway pressure (CPAP); 2) possible explanations of respiratory rate changes; 3) the effects of mouth opening. Two studies were conducted: a bench study using a manikin's head with lungs connected to a breathing simulator while delivering HFNC flow rates from 0 to 60L/min; a physiological cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…HFNC offers several physiological benefits in patients with acute respiratory failure by improving gas exchange and modulating inspiratory effort via the following mechanisms (1) flow-dependent small positive-pressure effect (up to 7 cm H 2 O with mouth closed [ 18 ]); (2) upper airway wash-out, reducing this part of the dead-space; (3) active heating and humidification, favoring comfort and airway mucosal integrity. A multicenter randomized trial [ 19 ] demonstrated that HFNC reduced the rate of endotracheal intubation in patients with moderate-to-severe hypoxemia compared to conventional oxygen therapy and facemask NIV and improved survival.…”
Section: High-flow Nasal Cannulamentioning
confidence: 99%
See 1 more Smart Citation
“…HFNC offers several physiological benefits in patients with acute respiratory failure by improving gas exchange and modulating inspiratory effort via the following mechanisms (1) flow-dependent small positive-pressure effect (up to 7 cm H 2 O with mouth closed [ 18 ]); (2) upper airway wash-out, reducing this part of the dead-space; (3) active heating and humidification, favoring comfort and airway mucosal integrity. A multicenter randomized trial [ 19 ] demonstrated that HFNC reduced the rate of endotracheal intubation in patients with moderate-to-severe hypoxemia compared to conventional oxygen therapy and facemask NIV and improved survival.…”
Section: High-flow Nasal Cannulamentioning
confidence: 99%
“…HFNC offers several physiological benefits in patients with acute respiratory failure by improving gas exchange and modulating inspiratory effort via the following mechanisms (1) flow-dependent small positive-pressure effect (up to 7 cm H 2 O with mouth closed [18]); (2) upper airway wash-out, reducing this part of the dead-space;…”
Section: High-flow Nasal Cannulamentioning
confidence: 99%
“…In absence of specific measurements, the last two observations could indicate enhanced expiratory resistance. This resistance could lead to the lower respiratory rate (RR) proved in the registry, a finding firmly demonstrated when HFO was applied in healthy volunteers by Brochard and coworkers 6 . In this paper, both inspiratory and expiratory resistance were measured accurately at different flow rates and increased significantly, reducing the RR, a fact that these authors warn should be taken into consideration in resistive patients (asthma, chronic obstructive pulmonary disease [COPD]).…”
Section: High-flow Nasal Therapymentioning
confidence: 75%
“…This resistance could lead to the lower RR proved in the registry, a finding firmly demonstrated when HFO was applied in healthy volunteers by Brochard and coworkers. 7 In this paper, both inspiratory and expiratory resistance were measured accurately at different flow rates and increases significantly, reducing the RR, a fact that these authors warn should be taken into consideration in resistive patients (Asthma, COPD). Then, the reduction in RR at higher flows would not represent a mechanical improvement as we might believe, rather a mechanical overload assumed by the patient.…”
mentioning
confidence: 97%